1999
DOI: 10.1046/j.1365-2958.1999.01652.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the protein InlB of Listeria monocytogenes and lipoteichoic acid: a novel mechanism of protein association at the surface of Gram‐positive bacteria

Abstract: SummaryInlB is a Listeria monocytogenes protein that is sufficient to promote entry in a variety of mammalian cells. The last 232-amino-acid domain (Csa) of InlB has been shown to mediate attachment on the listerial surface, although its sequence does not suggest any known mechanism of association to the bacterial surface. InlB is present both on the bacterial surface and in culture supernatants. As has been recently demonstrated, both forms of InlB, soluble and surfacebound, can trigger signalling in host cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
249
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(263 citation statements)
references
References 58 publications
9
249
1
2
Order By: Relevance
“…75 The GW modules of InlB mediate the binding of this protein to the bacterial surface by non-covalent interactions with LTAs. 37 The crystal structures of the LRR and LRR/IR domains and full-length protein indicate that InlB has a highly elongated structure, suggesting an interaction with multiple cell receptors, that cooperate in bacterial uptake. [76][77][78] Indeed, various host receptors have been identified for InlB: gC1qR, c-Met and glycosaminoglycans (GAGs).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 2 more Smart Citations
“…75 The GW modules of InlB mediate the binding of this protein to the bacterial surface by non-covalent interactions with LTAs. 37 The crystal structures of the LRR and LRR/IR domains and full-length protein indicate that InlB has a highly elongated structure, suggesting an interaction with multiple cell receptors, that cooperate in bacterial uptake. [76][77][78] Indeed, various host receptors have been identified for InlB: gC1qR, c-Met and glycosaminoglycans (GAGs).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Its C-terminal cell wall-anchoring (CWA) domain contains eight glycine-tryptophan (GW) modules, through which Ami associates to the bacterial surface, putatively by interaction with lipoteichoic acids (LTAs). [35][36][37] The CWA domain of Ami has been shown to mediate bacterial adhesion to human epithelial cells. 38,39 In addition, an ami mutant is attenuated in the liver of intravenously infected mice, suggesting a role in L. monocytogenes virulence.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…One set is composed of two proteins (LSA1159, LSA1165) containing an N-terminal cell-wall binding LysM domain (PF01476) and a C-terminal domain observed in autoaggregation-promoting factors of intestinal lactobacilli and enterococci 35 . The second set (LSA0194, LSA0313) are proteins containing a C-terminal cell-wall binding P60 domain (PF00877) and a N-terminal sequence of two repeated GW-like modules involved in lipoteichoic acid binding 36 . Each set is composed of one slightly acidic protein (pI 5.3-6.4; LSA0313 and LSA1159) and one highly basic protein (pI 4 8.9-8.7, LSA0194 and LSA1165) suggesting different binding properties or environment-dependent production (meat surface versus intestinal tract).…”
Section: Heme and Iron Requirementmentioning
confidence: 99%
“…It has been suggested that the hemodialysis procedures lower HBV DNA levels by various mechanisms: the clearance of HBV DNA by the dialysate, the entrapment of HCV DNA particles onto the membrane surface of dialyzers, and the production of cytokines and other substances during hemodialysis sessions. Rampino et al [29] have measured a prolonged and marked production of hepatocyte growth factor (HGF) during hemodialysis sessions, and have suggested a beneficial effect of HGF through hepatocyte proliferation and accelerated liver repair. Badalamenti et al [30] observed that IFN-alpha levels markedly increase after dialysis using both cellulose and synthetic membranes.…”
Section: Discussionmentioning
confidence: 99%